SWOT Analysis of Kendari Mayor’s Regulation Number 2 of 2023 on the Prevention and Control of Drug Abuse - Ramadhan Tosepu; Idaman Idaman; Danial Danial; Guswan Hakim; Fitrah Asfian (Yayasan Cipta Anak Bangsa (YCAB) Publisher, 2025)
Background: The abuse of narcotics, psychotropics, and other addictive substances (drugs) is a global problem that threatens public health and hinders socio-economic development. In Kendari City, the increasing misuse of drugs has prompted the issuance of Regional Regulation Number 2 of 2023 concerning the Facilitation of Prevention and Control of Drug Abuse and the Illicit Distribution of Narcotics. Objective: This study analyzes the implementation of Regional Regulation Number 2 of 2023 using SWOT (Strengths, Weaknesses, Opportunities, and Threats) analysis to evaluate the effectiveness of the policy and provide recommendations for improvement. Method: This study uses a descriptive qualitative method with a literature review approach. Data were obtained from regional regulatory documents and supporting literature. SWOT analysis was used to evaluate internal and external factors influencing policy implementation. Results: This regional regulation has strengths in the form of comprehensive rules, multi-stakeholder involvement, and clear funding through the Regional Budget (APBD). Its weaknesses include limited rehabilitation facilities, a lack of professional personnel, and challenges in inter-agency coordination. The opportunities lie in the potential for collaboration with the private sector and support from national programs. The threats faced include the increasing circulation of drugs, challenges in law enforcement, and social stigma toward addicts. Conclusion: Regional Regulation Number 2 of 2023 is a strategic step in the prevention and control of drug abuse in Kendari City. Its success requires strengthening facility capacity, improving inter-agency coordination, and promoting sustainable education. By integrating strengths and opportunities while addressing weaknesses and threats, this regulation has the potential to create a safe and drug-free environment. Keywords: Narcotics; Psychotropics; Addictive Substances; Narcotics Precursors; SWOT Analysis